2016
DOI: 10.1177/1557085116653181
|View full text |Cite
|
Sign up to set email alerts
|

Improving Identification of Strangulation Injuries in Domestic Violence: Pilot Data From a Researcher–Practitioner Collaboration

Abstract: Efforts to partner researchers and practitioners have the potential to significantly improve both research and response to non-fatal strangulation within the context of domestic violence. Non-fatal strangulation is far more common than most formal data suggest and is a highly gendered form of domestic assault often used to control or intimidate a partner; however, depending on how the assault takes place, it can leave little obvious physical evidence to an untrained investigator. The present study estimates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(88 citation statements)
references
References 51 publications
(122 reference statements)
6
80
1
1
Order By: Relevance
“…In line with the conclusions of Pritchard et al, (2018), the generally low prevalence of nonfatal strangulation seen in the current study and in Pritchard et al's (2018) research suggests that police officers may be overlooking incidents of strangulation among intimate partners. Given that visible injury is only seen in approximately half of strangulation cases, it seems plausible that officers may not be correctly identifying all nonfatal strangulation attacks.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In line with the conclusions of Pritchard et al, (2018), the generally low prevalence of nonfatal strangulation seen in the current study and in Pritchard et al's (2018) research suggests that police officers may be overlooking incidents of strangulation among intimate partners. Given that visible injury is only seen in approximately half of strangulation cases, it seems plausible that officers may not be correctly identifying all nonfatal strangulation attacks.…”
Section: Discussionsupporting
confidence: 89%
“…Using a police dataset consisting of 9,884 domestic incidents where stalking behavior was indicated, the current study found that the victim reported previous nonfatal strangulation in 16.6% of these incidents ( n = 1,638), a figure similar to other research based on police data (Pritchard et al, 2018). The prevalence of nonfatal strangulation among intimate partners varies within the research, often depending on the nature of the sample.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Finally, according to the FBI site for the SHR, NIBRS does not include drowning, pushed or thrown, or strangulation among the weapon types causing deaths, and the circumstances do not include sniper attacks, arguments over money or property, or Lover's triangles. Drowning and dying from being pushed or thrown are more likely to kill young children and the elderly (Huff‐Corzine et al., ), whereas strangulation is common among victims of intimate partner violence (Pritchard, Reckdenwald, & Nordham, ; Pritchard, Reckdenwald, Nordham, & Holton, ).…”
Section: Sources Of Official Data To Examine Mass Violencementioning
confidence: 99%